Study of Estimation Methane Emissions from Municipal Solid Waste Landfill Based on IPCC Model (Case Study: Klotok Landfill, Kediri) - Achmad C. Ni’am; Restu Hikmah Ayu Murti; Muhammad Abdus Salam Jawwad; Syadzadhiya Q. Z. Nisa (Universitas Diponegoro, 2022)
Sanitary landfill is the most common type of waste processing in Indonesia because it can minimize the negative impacts caused by waste and can utilize methane gas produced from the waste decomposition process. An analysis of the population projections of Kediri and waste generation was carried out to determine the waste generation at the Klotok Landfill. This study predicts methane gas emissions produced at the Klotok Landfill based on the IPCC method. This study uses two types of data: secondary and primary data. Secondary data includes the number of residents and waste entering the landfill, while the primary data used is waste composition. A sanitary landfill is needed in order to minimize the negative impact of solid waste, one of the negative impacts caused by solid waste is the formation of methane gas. This study uses the IPCC (Intergovernmental Panel Climate Change) model to calculate methane generation in the next ten years. The results show that population significantly impacts CH4 emissions from solid waste disposal facilities. Due to the city's growing urbanization and population increase, the production of waste in Kediri is increasing. Total waste production in 2032 is 723.98 m3/day or 217,195.44 Kg/day. In contrast, the total percentage of waste that goes to the Landfill is around 55%, so the waste that goes to the landfill is around 398.19 m3/day or 119.457.49 kg/day. In addition, the increase in the amount of solid waste at the Klotok landfill also produces methane gas. Based on the amount of waste that goes to the landfill, the projected methane gas formation from the IPCC model in 2032 can reach 6.148 Mg in a day.